Asuhan Keperawatan Keluarga pada Ny. S Keluarga Tn. N dengan Gangguan Sistem Endokrin: Diabetes Melitus di Dusun Bonjot Desa Kalibuntu RT 02 RW 04 Kecamatan Losari Kabupaten Brebes - Haya Izatul Jannah Suraya; Tati Karyawati; Arisnawati Arisnawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia still faces big challenges in developing public health. Changing people's lifestyles are one of the reasons for the shift in patterns from infectious diseases to non-communicable diseases (epidemiological transition). One of the non-communicable diseases that occupies the fourth position as the cause of death is diabetes mellitus, which was recorded as contributing 1.5 million cases in 2019 (Sarifah & Siyam, 2023). The signs and symptoms in diabetes mellitus patients are high blood sugar levels. The purpose of this writing is to find out and provide family nursing care to Mrs. S Family Mr. N With Endocrine System Disorders: Diabetes Mellitus in Bonjot Hamlet, Kalibuntu Village, RT 02 RW 04, Losari District, Brebes Regency, in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was found that Mrs. S complains of frequent urination. There were two diagnoses found, namely knowledge deficit and instability of blood glucose levels. Interventions are prepared based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.